2019
DOI: 10.1186/s12890-019-0982-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of ethambutol and rifampicin in the treatment of Mycobacterium avium complex pulmonary disease

Abstract: BackgroundA three-drug regimen (macrolide, ethambutol, and rifampicin) is recommended for the treatment of Mycobacterium avium complex pulmonary disease (MAC-PD). Although macrolide has proven efficacy, the role of ethambutol and rifampicin in patients without acquired immune deficiency syndrome is not proven with clinical studies. We aimed to clarify the roles of ethambutol and rifampicin in the treatment of MAC-PD.MethodsPatients treated for MAC-PD between March 1st, 2009 and October 31st, 2018 were reviewed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 35 publications
1
25
0
Order By: Relevance
“…Macrolides have been considered the cornerstone drugs in the treatment of MAC disease, followed by EMB and RIF ( Daley et al, 2020 ). Kim et al (2019) reported that MAC-PD patients who maintained treatment with either EMB or RIF with a macrolide had a higher probability of culture conversion than patients who maintained treatment with a macrolide only, but maintenance with EMB was superior to maintenance with RIF in terms of treatment outcomes and microbiological cure rates. In addition, Miwa et al (2014) reported that a double regimen without RIF was not inferior to a standard regimen with respect to culture conversion after 12 months of treatment in patients with MAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Macrolides have been considered the cornerstone drugs in the treatment of MAC disease, followed by EMB and RIF ( Daley et al, 2020 ). Kim et al (2019) reported that MAC-PD patients who maintained treatment with either EMB or RIF with a macrolide had a higher probability of culture conversion than patients who maintained treatment with a macrolide only, but maintenance with EMB was superior to maintenance with RIF in terms of treatment outcomes and microbiological cure rates. In addition, Miwa et al (2014) reported that a double regimen without RIF was not inferior to a standard regimen with respect to culture conversion after 12 months of treatment in patients with MAC.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with drug-susceptible MAC-PD generally receive at least three antibiotics, a macrolide [azithromycin or clarithromycin (CLR)], ethambutol (EMB), and rifampicin (RIF), as a standard regimen for at least 12 months based on previous empirical clinical investigations ( Griffith et al, 1996 ; Wallace et al, 1996 ; Wallace et al, 2014 ; Griffith, 2018 ). Although the clinical effectiveness of EMB and RIF in MAC-PD treatment has not been fully verified, these drugs are used as supportive treatments to prevent microbiological resistance to macrolide monotherapy ( Kim et al, 2019 ). In addition, the minimum inhibitory concentrations (MICs) of EMB and RIF are associated with treatment efficacy, and 85.3% of patients whose MAC isolates have MICs of <8 mg/L for RIF and/or EMB have successful treatment ( Kwon et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…NTM-PD due to MAC is treated with a drug regimen comprising rifampicin (or rifabutin in HIV-positive individuals to avoid drug-drug interactions 19 ), ethambutol and macrolide (azithromycin or clarithromycin; some patients tolerate azithromycin better) 1 17 . There is an in vitro synergy of antimycobacterial action between rifampicin and ethambutol as the latter destabilizes mycobacterial cell wall and facilitates rifampicin entry into the Mycobacteria to its target site, the RNA polymerase 149 150 . These two drugs also prevent development of macrolide resistance 151 .…”
Section: Treatment Of Ntm Diseasementioning
confidence: 99%
“…In vitro synergy has been demonstrated with rifamycins and ethambutol, in which the combination MICs for both drugs are significantly lower than when evaluated separately. While the clinical relevance of this in vitro synergy has come into question [ 62 ], multiple studies have demonstrated more favorable clinical outcomes when the 2 drugs are combined for MAC infections [ 63 ]. As such, it is recommended to include ethambutol with rifampin or rifabutin for optimal management of M. chimera infections [ 26 ].…”
Section: Pharmacologic Managementmentioning
confidence: 99%